Rural Aboriginal high school students' views of their future tertiary education - Howard, Jessica; Jeffery, Jacob; Walters, Lucie; Barton, Elsa (The Australian Journal of Indigenous Education, 2020)
Abstract In the context of a stark discrepancy in the educational outcomes of Aboriginal Australians compared to non-Aboriginal Australians, this article aims to contribute the voices of rural Aboriginal high school students to the discourse. This article utilises an appreciative enquiry approach to analyse the opinions and aspirations of 12 Aboriginal high school students in a South Australian regional centre. Drawing on student perspectives from semi-structured interviews, this article contributes to and contextualises the growing body of literature regarding educational aspirations. It demonstrates how rurality influences a complex system of intrinsic attributes, relationship networks and contextual factors. It offers an important counterpoint to discourses surrounding academic disadvantage and highlights the lived experience of rural Aboriginal Australians.